2013
DOI: 10.1016/j.image.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia search and retrieval using multimodal annotation propagation and indexing techniques

Abstract: In this paper, a novel framework for multimodal search and retrieval of rich media objects is presented. The searchable items are media representations consisting of multiple modalities, such as 2D images, 3D objects and audio files, which share a common semantic concept. A manifold learning technique based on Laplacian Eigenmaps was appropriately modified in order to merge the low-level descriptors of each separate modality and create a new low-dimensional multimodal feature space, where all media objects can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…One class of models are based on combination strategies: (1) combining low-level features from different modalities into concise multi-modal features. In [12], a manifold learning algorithm based on Laplacian Eigenmaps is introduced to combine low-level descriptors of each separate modality and map them to a new low-dimensional multi-modal feature space. In this feature space, semantically similar multi-modal data are represented by multi-modal descriptor vectors close to each other.…”
Section: Related Workmentioning
confidence: 99%
“…One class of models are based on combination strategies: (1) combining low-level features from different modalities into concise multi-modal features. In [12], a manifold learning algorithm based on Laplacian Eigenmaps is introduced to combine low-level descriptors of each separate modality and map them to a new low-dimensional multi-modal feature space. In this feature space, semantically similar multi-modal data are represented by multi-modal descriptor vectors close to each other.…”
Section: Related Workmentioning
confidence: 99%
“…Hierarchical image partitioning method is used to detect scale of a live image by matching this image with the database images. Lazaridis et al (2013) designed a method to search and retrieve multimodal data. This framework links images to semantic annotation using some similarity measure.…”
Section: Related Workmentioning
confidence: 99%
“…The main difficulty in cross-media retrieval is to define a similarity measure among heterogeneous low-level features. In order to simultaneously search and retrieve data from multiple modalities, other approaches have been considered [10,11,12,13,14,15,16,17,18,19,20]. For instance in [16], it is experimentally shown that multimodal queries achieve higher retrieval accuracy than mono-modal ones.…”
Section: Introductionmentioning
confidence: 99%
“…The work in [10] suggests using a combination of ontology browsing and keyword-based querying. The methods presented in [11,14,15,16] use a similar approach and rely on the assumption that every document has an equal number of nearest neighbors for each of the modalities. However, such an assumption might degrade the retrieval performance as a document containing "image+text" may have many nearest neighbors in image modality, but not as many relevant textual data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation